Efektivitas Pemberian Terapi Buteyko Terhadap Perubahan Status Pernapasan Pada Pasien Asma Bronchial Di Wilayah Kerja Puskesmas Kemiling Bandar Lampung Tahun 2025 - Eka Trismiyana; Walenda Pitri Novidia Sari; Rika Yulendasari (Sekolah Tinggi Ilmu Kesehatan Panca Bhakti, 2026)
Introduction: Asthma is a clinical disease characterized by recurrent bronchial narrowing; however, this condition is reversible, and increased ventilation occurs between episodes of normal bronchial constriction. The Buteyko breathing technique is a breathing method that involves nasal breathing. This technique is used to reduce shortness of breath experienced by patients with bronchial asthma. According to data from Riskesda Lampung Province in 2023, approximately 1.6% of cases were asthma, and Lampung ranked 4th with a recurrence rate of 64.7% .Objective: To determine the effectiveness of Buteyko therapy on changes in respiratory status in patients with bronchial asthma in the working area of Puskesmas Kemiling, Bandar Lampung, in 2025. Method: This quantitative study used a quasi-experimental design with a one-group pretest-posttest approach. The population included all asthma patients diagnosed between January and October 2024, totaling 221 patients. The sample size, calculated using Slovin’s formula, was 23 respondents. Non-probability sampling with convenience sampling was applied. Results: The average respiratory rate of asthma patients before Buteyko therapy was 23.28 ± 1.410. After receiving Buteyko therapy, the average respiratory rate decreased to 16.23 ± 1.756. The paired t-test showed a significant difference in respiratory rates before and after the intervention (p = 0.000). Conclusion: Buteyko therapy has a significant effect in reducing shortness of breath in asthma patients in the working area of Puskesmas Kemiling, Bandar Lampung. The respiratory rate decreased from 23–28 before the intervention to 16–23 after the intervention. Recommendation: It is recommended that respondents better understand the importance of performing Buteyko therapy to help alleviate asthma symptoms.